Evaluation of CHROMagar Candida Plus for the detection of C. auris with a panel of 206 fungal isolates and 83 colonization screening skin-swabs - Meghan L. Bentz; Ngoc Le; Brian Min; Natalie S. Nunnally; Vickie Sullivan; Mike Tran; Shawn R. Lockhart; Ana Litvintseva; Elizabeth L. Berkow; D. Joseph Sexton (Microbiology Spectrum, 2024)
ABSTRACTCHROMagar Candida Plus is a new formulation of chromogenic media designed for the detection and differentiation of major clinical Candida species, including Candida auris. The objective of this study is to evaluate CHROMagar Candida Plus when used according to manufacturer’s instructions with a panel of 206 fungal isolates and 83 skin-swab specimens originally collected for C. auris colonization screening. Of the 68 C. auris isolates tested, 66/68 displayed the expected light-blue colony morphology and blue halo within 48 h. None of the remaining 138 non-auris isolates appeared similar to C. auris. CHROMagarCandida Plus was, therefore, inclusive to 97% of 68 C. auris isolates tested and supported visual exclusion of 100% of the 138 non-C. auris isolates tested. For the 83 colonization screening specimens, direct plating onto CHROMagarCandida Plus was 60% sensitive and 100% specific when compared to the enrichment broth gold-standard reference method. In sum, these findings demonstrate the utility of this media when working with isolates but also notable limitations when working with primary skin-swabs specimens when competing yeast species are present.IMPORTANCECandida auris is an emerging fungal pathogen of public health concern. As it continues to spread, it is important to publish evaluations of new diagnostic tools. In this study, we share our experience with a new chromogenic media which can help distinguish C. auris from related species.